BIOAKUMULASI KADMIUM PADA KERANG HIJAU (PERNA VIRIDIS) DENGAN APLIKASI PERUNUT RADIOAKTIF - Siregar, Yusni Ikhwan (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTBioacumulation of Cadmium on Green Mussel (Perna viridis) Using Radiotracer. A laboratoryexperiment on the accumulation of Cadmium (Cd) by green mussel (Perna viridis) has beenconducted. Radiotracer 109Cd was applied in the study. The research aimed at evaluating theeffect of salinity, temperature and size on uptake of radiotracer 109Cd by green mussel (Pernaviridis) from dissolved phase. It was found that both salinity and temperature had significanteffect ( P< 0.001) on accumulation rate of 109Cd. The highest concentration factor of Cd (31,23-54,09) was appeared in water salinity of 29% and of water temperature 30oC. At the steady statecondition green mussel accumulated 72,21-107,80 Bq/gr Cd. It revealed that the small Pernaviridis (5.2 cm in length) accumulated 109Cd about 107,80 Bq/gr, whereas the bigger size ofPerna viridis (6.6 cm in length) had an uptake of about 72,21 Bq/gr.Key words : Bioaccumulation, radiotracer Cd, Perna viridisKata kunci : Bioakumulasi, Perunut radioaktif, Cd, Perna viridis